Film Televisi (FTv): Sistem Industri Televisi Yang Membentuk Pengetahuan Penonton - Nesia Putri Amarasthi (Arete, 2017)
This research will take the material object Television Film. Researchers will focus on the topic of Television Film as a language agent. Some points that can be concluded from this research are: First, television has a system in its relation to the mass industry. Television becomes an agent of change. It should be highlighted that this change could be the marginalization and production of perceptions of second-level language systems. Second, television films have a high rating for teens and young people. It means that television films have a good position in the hearts of the audience. Meanwhile, the production of the FTV event does not consider the impact. Third, the language in television films has the most important role of turning a sign system. Fourth, in this paper, knowledge is produced massively on the industrial systems. Fifth, the FTV show controls over the mass culture